Utilization of sewage sludge from acid casein production for soil fertilization - Zuokaitė, Eglė; Ščupakas, Davidas (Journal of Environmental Engineering and Landscape Management, 2007)
Organic biodegradable waste composes a fair part of farm and vital activity waste. The disposal of this waste in municipal waste landfills pollutes the environment and soil. Therefore, the European Union and other countries look for alternatives to manage biodegraded waste. This paper seeks to analyse the properties of sludge that forms in the sewage treatment plants of the acid casein production, examines experience in managing and applying sludge. The results of an experiment show that sewage sludge from the acid casein production is suitable as a soil fertilizer for growing lettuce (Lactuca sativa L.) and garden cress (Lepidium sativum L.). After soil was fertilized with this sludge, the germination of lettuce and garden cress as well as the biomass of experimental alimentary plants increased. A suitable ratio of soil and sludge mixture was determined (for lettuce ‐ 1:1, for garden cress ‐ 3:1). Potassium sulphate which was added to a soil‐sludge mixture improved the values of fertility parameters of alimentary plants.Rūgštinio kazeino gamybos nuotekų dumblo naudojimas dirvožemiui tręštiSantrauka. Organinėms biodegraduojamoms atliekoms tenka nemaža ūkinės ir gyvybinės veiklos atliekų dalis. Jų deponavimas komunalinių atliekų sąvartynuose yra susijęs su aplinkos ir dirvožemio tarša. Todėl Europos Sąjungos ir kitose pasaulio šalyse ieškoma tinkamų alternatyvų biodegraduojamoms atliekoms tvarkyti. Išnagrinėtos rūgštinio kazeino gamybos nuotekų valymo įrenginiuose susidarančio dumblo savybės, apžvelgta dumblo tvarkymo ir naudojimo patirtis. Atlikus eksperimentą, nustatyta, kad rūgštinio kazeino gamybos nuotekų dumblas tinka dirvožemiui tręšti auginant salotas (Lactuca sativa L.) ir sėjamąsias pipirnes (Lepidium sativum L.). Patręšus dirvožemį šiuo dumblu, padidėjo salotų ir pipirnių daigumas, išauginta didesnė bandomųjų maistinių augalų biomasė. Nustatytas tinkamiausias dirvožemio ir dumblo mišinio santykis (salotoms − 1:1, pipirnėms − 3:1). Į dirvožemio ir dumblo mišinį pridėjus kalio sulfato, pagerėjo maistinių augalų derlingumo parametrų vertės.Reikšminiai žodžiai: rūgštinis kazeinas, nuotekų dumblas, tręšimas.Применение ила сточных вод после производства кислотного казеина для удобрения почвыРезюме. Биологически деградирующие органические отходы составляют немалую часть отходов от хозяйственной деятельности и жизнедеятельности. Хранение их в коммунальных мусорных свалках вызывает загрязнение среды и почвы. Потому в Евросоюзе и других странах мира ведутся поиски альтернативных вариантов для очищения биологически деградирующих отходов. В статье рассмотрены свойства ила, образующегося в очищающих установках сточных вод, а также опыт по очистке и применению ила. В результате зксперимента установлено, что ил сточных вод после производства кислотного казеина можно применять для удобрения почвы при выращивании салата (Lactuca sativa L.) и кресс-салата (Lepidium sativum L.). После удобрения почвы этим илом увеличилась растительность салата и кресс-салата, выращено больше биомассы пробных пищевых растений. Установлено приемлемое соотношение почвы и ила (для салата – 1:1, кресс-салата – 3:1). После прибавления в смесь почвы и ила сульфата калия улучшились значения параметров урожайности пищевых растений.Ключевые слова: кислотный казеин, ил сточных вод, удобрение.First Published Online: 14 Oct 2010